Tooth Necklace (2023)
Tooth Necklace takes inspiration in the act of consumption (both metaphorical and literal). The rhythms and timbres are taken from transcribing source recordings of chewing and swallowing and the resultant texture is orchestrated "hocket-like" throughout the ensemble. The unrelenting nature of this music creates this image in my mind where the ensemble functions as some imaginary creature or being that is consuming the audience.